ASSOCIATION BETWEEN CATARACT SURGERY AND AGE-RELATED MACULAR DEGENERATION: A SYSTEMATIC REVIEW - Anggarini, Dwi Wening (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: As a leading cause of visual impairment in elderly, age-related macular degeneration has an increasing global incidence annually. It’s association towards cataract surgery remains a debate. Aim: The objective of this study is to summarize and evaluate the association between cataract surgery and age-related macular degeneration. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, ProQuest) and included articles published between 2018–2023. Duplicate publications, review articles, and incomplete articles were excluded. Results: Databases searching identified a total of 254 articles. Of these, 29 articles passed the screening process and resulted in 12 articles for full-text assessment. The 6 articles did not evaluate the outcome of interest. Hence, we found six appropriate studies included in this review. Conclusion: The results suggest that there may be an association of cataract surgery and increased risk of AMD progression and development. This association may increase according to the time of follow-up since cataract surgery. To improve medical treatment and for patients with cataract and AMD, additional research is essential to increase understanding of the disease state and its impact on AMD progression mainly prospective multicenter and RCT studies.